LSMS+ Program in Cambodia : Findings from Individual-Level Data Collection on Labor and Asset Ownership - Hasanbasri, Ardina; Kilic, Talip; Koolwal, Gayatri; Moylan, Heather (World Bank, Washington, DC, 2021)
Established in 2016, the World Bank living standards measurement study - plus (LSMS+) program works to enhance the availability and quality of intra-household, self-reported, individual-disaggregated survey data collected in low- and middle-income countries on key dimensions of men’s and women’s economic opportunities and welfare. This report presents findings on gender differences in labor market outcomes and ownership of physical and financial assets in Cambodia, based on a national survey that was implemented by the National Institute of Statistics (NIS) in 2019, with support from the LSMS+ program.